2021
DOI: 10.1021/acs.jmedchem.1c00507
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a First-in-Class Inhibitor of the PRMT5–Substrate Adaptor Interaction

Abstract: PRMT5 and its substrate adaptor proteins (SAPs), pICln and Riok1, are synthetic lethal dependencies in MTAP-deleted cancer cells. SAPs share a conserved PRMT5 binding motif (PBM) which mediates binding to a surface of PRMT5 distal to the catalytic site. This interaction is required for methylation of several PRMT5 substrates, including histone and spliceosome complexes. We screened for small molecule inhibitors of the PRMT5–PBM interaction and validated a compound series which binds to the PRMT5–PBM interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Also, viral proteins from several viruses are methylated by PRMTs, including SARS-CoV-2 nucleocapsid (N) protein, the methylation of which at residues R95 and R177 is crucial for viral replication . Indeed, over the past 15 years the medicinal chemistry community has paid a growing attention to PRMTs, ,, in particular to PRMT5 (with a few inhibitors in clinical trials) , and to type I enzymes (both pan-type I , and selective , ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, viral proteins from several viruses are methylated by PRMTs, including SARS-CoV-2 nucleocapsid (N) protein, the methylation of which at residues R95 and R177 is crucial for viral replication . Indeed, over the past 15 years the medicinal chemistry community has paid a growing attention to PRMTs, ,, in particular to PRMT5 (with a few inhibitors in clinical trials) , and to type I enzymes (both pan-type I , and selective , ).…”
Section: Introductionmentioning
confidence: 99%
“…This inhibitor was shown to effectively outcompete binding between PRMT5 and RIOK1, inhibiting the methylation of certain PRMT5 substrates dependent on RIOK1 interaction. 135 A new potent and selective PRMT5 inhibitor that binds to the MTA-bound PRMT5 complex has also been developed. MRTX1719 has been shown to inhibit PRMT5 activity exclusively in MTAP negative cells.…”
Section: Prmt Inhibitors In the Treatment Of Immune And Inflammatory-...mentioning
confidence: 99%
“…PRMT5 consists of two binding pockets in the SAM-dependent methyltransferase domain, including a SAM binding pocket and a substrate peptide binding pocket, which provide two options for the development of PRMT5 inhibitors. Indeed, many efforts have been made to discover PRMT5 inhibitors by targeting one of these two pockets. As shown in Figure , compound 2 ( EPZ015666 ) is the first reported highly potent and orally bioavailable PRMT5 inhibitor, with an IC 50 of 22 nM in a biochemical assay . Kinetic experiments showed that it was competitive with the peptide substrate and uncompetitive with SAM.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, synthetic lethal inhibitors of the PRMT5 . MTA complex were discovered for the treatment of MTAP-deleted cancers, providing an option for therapeutic intervention. ,− …”
Section: Introductionmentioning
confidence: 99%